A low-hysteresis and high-toughness soybean protein adhesive and its preparation method and application

By introducing chain tangled structure and metal coordination of calcium sulfa aluminate in soy protein adhesive, the soy protein-polyacrylamide chain tangled polymer is constructed, which solves the problems of brittle glue layer and weak interface force, and achieves low hysteresis, high toughness and high interface force, improving the glue performance and durability of artificial boards.

CN117659940BActive Publication Date: 2025-04-15INST OF CHEM IND OF FOREST PROD CHINESE ACAD OF FORESTRY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311607904.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-29
Publication Date
2025-04-15
Estimated Expiration
2043-11-29

AI Technical Summary

Technical Problem

The existing water-based polyamide epoxy modified soy protein adhesives have complex protein structure and many hydrophilic groups, resulting in brittle glue layer, poor water resistance, large molecular weight and poor permeability. They fail to form effective "glue nails" at the wood interface, resulting in unstable glue performance, limiting their application in high-demand artificial board manufacturing.

Method used

By introducing a chain tangle structure into the soy protein adhesive, the metal coordination effect of calcium sulfa aluminate hydrate is used to induce entanglement of polyacrylamide macromolecular chains, soy protein-polyacrylamide chain tangle polymers are constructed, the toughness of the glue layer is improved, and hydrogen bonds are formed with wood through polyacrylamide chain tangle to enhance the interface force.

Benefits of technology

A low-hysteresis and high-toughness soy protein adhesive is achieved, the tear can reach 4100J/m2, the tensile stress is reached 453kPa, and the interface force with the wood is significantly improved, which improves the bonding performance and durability of artificial boards.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117659940B_ABST
    Figure CN117659940B_ABST
Patent Text Reader

Abstract

The present invention discloses a low-hysteresis and high-toughness soy protein adhesive and its preparation method and application. The metal coordination effect of calcium sulfoaluminate hydrate is used to induce entanglement of polyacrylamide macromolecular chains, so as to construct a soy protein-polyacrylamide chain entanglement polymer, and transmit external stress and dissipate energy through the sliding of entanglement sites, so as to improve the toughness of the adhesive layer under low hysteresis; at the same time, the polyacrylamide chain entanglement formed at the wood interface forms a large number of hydrogen bonds with the wood and the adhesive layer, respectively, to generate strong binding energy, thereby improving the interfacial force between the adhesive and the wood. The present invention introduces a chain entanglement structure into the soy protein adhesive system to construct a network structure in which protein and chain entanglement polymer are integrated, which helps to solve the problem that the adhesive cured adhesive layer is brittle and the interfacial force with the wood is weak, and provides technical support for improving the quality of artificial board products and promoting the large-scale application of soy protein adhesives.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of adhesives, and in particular relates to a soybean protein adhesive with low hysteresis and high toughness, and a preparation method and application thereof. Background Art

[0002] As people's requirements for indoor environment and healthy life increase, the use of bio-based adhesives to manufacture high-quality environmentally friendly wood-based panels has become an important development direction of the wood industry. At present, soy protein adhesives have become an important variety and research hotspot of bio-based wood adhesives due to their advantages such as abundant raw materials, low cost and no harmful substances released.

[0003] At present, soybean protein adhesives have been industrially applied mainly in the bonding of particleboard surface, core layer of blockboard, and ordinary floor substrate. However, compared with traditional "trialdehyde" adhesives, the water-based polyamide epoxy-modified soybean protein adhesives currently used in the wood industry have problems such as brittle adhesive layer and poor water resistance due to complex protein structure and multiple hydrophilic groups. Due to large molecular weight and poor permeability, they fail to form effective "glue nails" at the wood interface, resulting in weak interfacial force with wood, and unstable bonding performance of wood-bonded products, which restricts its application in the manufacture of artificial boards such as geothermal floors, high-density fiberboards, and super-strong particleboard core layers, which require high adhesive penetration, durability, and bonding strength. Therefore, research and development of highly adhesive soybean protein adhesives is of great significance to improving the quality of artificial board products, realizing large-scale application of soybean protein adhesives, and promoting the environmental quality upgrade of the artificial board industry.

[0004] The bonding strength of traditional soy protein adhesives mainly comes from weak intermolecular forces such as hydrogen bonds between protein molecules and between protein and wood, which leads to low bonding strength and poor water resistance. Based on this, researchers have proposed a variety of modification methods for soy protein adhesives in recent years, mainly focusing on the modification of protein molecules, including: (i) using physical, acid-base, surfactant and other methods to destroy the quaternary structure of protein molecules, so that the polar groups inside the molecules are exposed, and the covalent bonds between protein molecules are used to improve the bonding strength of adhesives; (ii) using the grafting method to introduce active groups into protein molecules, improve the reactivity of proteins to promote the formation of cross-linked structures, thereby enhancing the bonding performance of adhesives; (iii) by adding cross-linking agents, the active groups such as epoxy, isocyanate, catechol, carboxyl in the cross-linking agent react with amine, carboxyl, hydroxyl and other groups in the soy protein molecules to form cross-linked structures to improve the bonding strength of adhesives. At present, the research and development of soy protein adhesives has made certain progress, but there are still two major defects: on the one hand, the modified soy protein adhesive has increased its cohesive strength due to the increased crosslinking density, but at the same time it causes the brittleness of the cured adhesive layer to increase, which in turn leads to the adhesive layer being prone to cracking due to lack of toughness, resulting in poor impact resistance and easy debonding and deformation of the bonded products; on the other hand, the interaction between the adhesive and the wood mainly comes from the intermolecular interaction such as hydrogen bonds between the protein and the wood surface. This weak interfacial interaction has a very limited contribution to the bonding strength, and the bonded products are prone to defects such as interfacial cracking caused by stress concentration during use. Therefore, how to improve the toughness of the soy protein adhesive and improve the interface interaction with the wood is the key to solving the above problems.

[0005] In recent years, researchers have proposed a variety of methods for toughening polymer materials. The core strategy is to improve the toughness of materials by introducing various energy dissipation mechanisms into the polymer matrix, including: (i) constructing a double cross-linked network, using the short chain segments in the high cross-linked network to dissipate energy by breaking, and the long chain segments in the low cross-linked network to transfer stress and induce more short chain segments to break; (ii) introducing physical cross-linking, such as interionic forces, host-guest interactions, hydrogen bonds, hydrophobic effects, etc., to dissipate energy through the reversible cross-linking of polymer segments; (iii) introducing specific biomacromolecules or force-sensitive units into the cross-linked structure, and using the transformation of the molecular chain domain to dissipate mechanical energy. Although the above methods can make the material tougher to a certain extent, at the same time, during the loading-unloading process, due to the large amount of energy dissipated by the breaking of covalent or non-covalent bonds, the polymer chain produces obvious stress-strain hysteresis. The toughness obtained by high hysteresis cannot effectively inhibit crack propagation, thereby weakening the material's fatigue resistance and mechanical stability. When the above method is used for toughening and modifying soybean protein adhesive, it is easy to cause crack propagation in the cured adhesive layer due to hysteresis, thereby resulting in reduced bonding performance and durability of adhesive products such as artificial boards, easy deformation of the boards, and affecting the long-term stability of the boards. Summary of the invention

[0006] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.

[0007] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.

[0008] Therefore, the object of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing a soybean protein adhesive with low hysteresis and high toughness.

[0009] In order to solve the above technical problems, the present invention provides the following technical solutions: a method for preparing a low-hysteresis and high-toughness soybean protein adhesive, comprising:

[0010] The soy protein powder is mixed with distilled water to obtain a mixed solution, and the mixed solution is subjected to a heating treatment to obtain a soy protein water dispersion;

[0011] At room temperature, acrylamide and ammonium persulfate are dissolved in distilled water, and fully stirred to dissolve to obtain an acrylamide prepolymer solution;

[0012] Dropping the acrylamide prepolymer solution into the soy protein aqueous dispersion, stirring and fully mixing at room temperature, to obtain a soy protein-acrylamide prepolymer;

[0013] At room temperature, adding inorganic calcium sulfoaluminate powder to the soy protein-acrylamide prepolymer and fully dispersing it to obtain a soy protein-acrylamide-hydrated calcium sulfoaluminate water dispersion;

[0014] The soy protein-acrylamide-calcium sulfoaluminate hydrate aqueous dispersion is allowed to stand at room temperature for 2 to 4 hours. The calcium sulfoaluminate undergoes a hydration reaction to generate calcium sulfoaluminate hydrate nanocrystals and releases heat. The acrylamide monomer undergoes thermal polymerization to generate polyacrylamide macromolecular chains. The Al 3+ , Ca 2+ Through coordination, the polyacrylamide macromolecular chains are induced to entangle around the crystals, forming polyacrylamide chain entanglements with calcium sulfoaluminate hydrate as the entanglement sites. At the same time, the carboxyl groups on the soy protein particles are aggregated around the polyacrylamide chains through intermolecular forces, forming soy protein-polyacrylamide chain entanglement polymers.

[0015] As a preferred embodiment of the preparation method of the present invention, wherein: the soy protein powder is mixed with distilled water to prepare a mixed liquid, wherein the concentration of the soy protein in the mixed liquid is 0.2-0.3 g / mL.

[0016] As a preferred embodiment of the preparation method of the present invention, the soy protein water dispersion is obtained by heating at a temperature of 90 to 95° C. and stirred for 4 to 5 hours.

[0017] As a preferred embodiment of the preparation method of the present invention, acrylamide and ammonium persulfate are dissolved in distilled water, wherein the mass ratio of acrylamide to ammonium persulfate is 1:0.006 to 1:0.02, and the concentration of acrylamide in the acrylamide prepolymer solution is 0.5 to 1 g / mL.

[0018] As a preferred embodiment of the preparation method of the present invention, the inorganic calcium sulfoaluminate powder is added to the soy protein-acrylamide prepolymer, wherein the mass ratio of the calcium sulfoaluminate powder to acrylamide is 2 to 20:100.

[0019] Another object of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing a low hysteresis and high toughness soy protein adhesive, wherein the soy protein adhesive has a hysteresis of less than 6% and a tear energy of 4100 J / m 2 , tensile stress reaches 453kPa.

[0020] Another object of the present invention is to overcome the deficiencies in the prior art and provide a soy protein adhesive with low hysteresis and high toughness for use as an adhesive in wood.

[0021] Beneficial effects of the present invention:

[0022] (1) The present invention provides a method for preparing a soybean protein adhesive with low hysteresis and high toughness, wherein the metal coordination effect of calcium sulfoaluminate hydrate nanocrystals is used to induce directional entanglement of polyacrylamide macromolecular chains, thereby constructing a new soybean protein adhesive with a chain entanglement structure; in the soybean protein-polyacrylamide polymer network, the sliding of the entanglement sites is used to transmit external stress and dissipate energy, thereby achieving the improvement of the toughness and fatigue resistance of the adhesive at the same time under low hysteresis; at the same time, when the adhesive is used for wood bonding, part of the acrylamide prepolymer penetrates and diffuses on the wood surface, and is polymerized in situ to form polyacrylamide chain entanglements, which span the bonding interface and penetrate the wood and the glue layer. Since the polyacrylamide chain entanglements at the wood interface form a large number of hydrogen bonds with the wood and the glue layer, respectively, strong binding energy is generated, thereby improving the interfacial interaction between the adhesive and the wood.

[0023] (2) The present invention introduces a chain entanglement structure into the soy protein adhesive system to construct a network structure integrating protein and chain entanglement polymer, which helps to solve the problems of brittle adhesive layer and weak interaction force with wood interface after adhesive curing, and provides technical support for improving the quality of artificial board products and promoting the large-scale application of soy protein adhesive.

[0024] (3) The preparation process of the present invention is simple, does not use organic solvents, has low energy consumption, is easy to produce in large quantities, and is conducive to industrial application and promotion. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:

[0026] Figure 1 3 and 4 are microscopic morphology and mechanical properties diagrams of the soybean protein-polyacrylamide chain entanglement polymer in the embodiment of the present invention, wherein a is a three-dimensional tomography image of the polymer, and bd is a scanning electron microscope and element distribution image of the gel.

[0027] Figure 2 Graph showing the tensile properties of the soy protein-polyacrylamide chain entanglement polymer gel in an embodiment of the present invention, wherein a is a tensile stress-strain curve of the polymer gel, and b is a comparison graph showing the Young's modulus, fracture stress and fracture strain of the polymer gels of different embodiments.

[0028] Figure 31 is a toughness diagram of the soy protein-polyacrylamide chain entanglement polymer gel in an embodiment of the present invention, wherein ae is the tension-displacement curve of the polymer gel, and f is a tear energy comparison diagram of the polymer gels in different embodiments.

[0029] Figure 4 3 is the anti-fatigue and hysteresis diagram of the soybean protein-polyacrylamide chain entanglement polymer gel in the embodiment of the present invention, wherein a is the stress-strain curve of the polymer gel after 100 cycles of stretching, and b is the maximum stress, plastic deformation rate and energy dissipation coefficient of the polymer gel during 100 cycles of stretching.

[0030] Figure 5 : These are the application performance diagrams of the soybean protein adhesive on the eucalyptus veneer in the embodiments of the present invention, wherein a is the coating performance diagram of the ordinary soybean protein adhesive, b is the coating performance diagram of the modified soybean protein adhesive, and c is a mechanical properties comparison diagram of the three-layer eucalyptus plywood prepared by the adhesive.

[0031] Figure 6 It is a comparison diagram of the mechanical properties of the soybean protein-polyacrylamide chain entanglement polymers prepared in Comparative Example 1 and Comparative Example 2 of the present invention, wherein a is the tear energy diagram of the polymer gel, and b is the maximum stress, plastic deformation rate and energy dissipation coefficient diagram during the stretching process of the polymer gel. DETAILED DESCRIPTION

[0032] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.

[0033] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0034] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0035] In the present invention, soybean protein: Macklin reagent; acrylamide: Aladdin reagent; ammonium persulfate: Sigma-Aldrich reagent; calcium sulfoaluminate: Wuxi Yangshijin Building Materials Co., Ltd.

[0036] Example 1

[0037] This embodiment provides a method for preparing a soybean protein-polyacrylamide chain entanglement polymer, the main steps of which are:

[0038] (1) In a 250 mL stirred reactor, 20 g of soybean protein powder was dissolved in 100 mL of distilled water and stirred at room temperature for 1 h to fully soak the soybean protein powder;

[0039] After heat denaturation at 90°C for 4 h, a light yellow soy protein aqueous dispersion was obtained;

[0040] (2) dissolving 20 g of acrylamide monomer and 0.12 g of ammonium persulfate initiator in 40 mL of distilled water and stirring the mixture at room temperature for 1 h to obtain an acrylamide prepolymer solution;

[0041] (3) then dropping the acrylamide prepolymer solution into the soybean protein aqueous dispersion, stirring at room temperature for 1 hour, and fully mixing to obtain a soybean protein-acrylamide prepolymer;

[0042] (4) adding 0.4 g of calcium sulfoaluminate to the soy protein-acrylamide prepolymer and hydrating for 30 min to obtain a soy protein-acrylamide-hydrated calcium sulfoaluminate aqueous dispersion;

[0043] (5) The dispersion was allowed to stand at room temperature for 4 h to thermally initiate free radical polymerization of acrylamide to generate soybean protein-polyacrylamide chain entanglement polymers.

[0044] Example 2

[0045] This embodiment provides a method for preparing a soybean protein-polyacrylamide chain entanglement polymer, the main steps of which are:

[0046] (1) In a 250 mL stirred reactor, 25 g of soybean protein powder was dissolved in 100 mL of distilled water and stirred at room temperature for 1 h to fully soak the soybean protein powder;

[0047] After heat denaturation at 90°C for 4 h, a light yellow soy protein aqueous dispersion was obtained;

[0048] (2) dissolving 25 g of acrylamide monomer and 0.2 g of ammonium persulfate initiator in 40 mL of distilled water and stirring the mixture at room temperature for 1 h to obtain an acrylamide prepolymer solution;

[0049] (3) then dropping the acrylamide prepolymer solution into the soybean protein aqueous dispersion, stirring at room temperature for 1 hour, and fully mixing to obtain a soybean protein-acrylamide prepolymer;

[0050] (4) adding 1.25 g of calcium sulfoaluminate to the soy protein-acrylamide prepolymer and hydrating for 30 min to obtain a soy protein-acrylamide-hydrated calcium sulfoaluminate aqueous dispersion;

[0051] (5) The dispersion was allowed to stand at room temperature for 3.5 h to thermally initiate free radical polymerization of acrylamide to generate soybean protein-polyacrylamide chain entanglement polymers.

[0052] Example 3

[0053] This embodiment provides a method for preparing a soybean protein-polyacrylamide chain entanglement polymer, the main steps of which are:

[0054] (1) In a 250 mL stirred reactor, 25 g of soybean protein powder was dissolved in 100 mL of distilled water and stirred at room temperature for 1 h to fully soak the soybean protein powder; heat denaturation was performed at 90° C. for 4 h to obtain a light yellow soybean protein water dispersion;

[0055] (2) dissolving 30 g of acrylamide monomer and 0.36 g of ammonium persulfate initiator in 40 mL of distilled water and stirring the mixture at room temperature for 1 h to obtain an acrylamide prepolymer solution;

[0056] (3) adding the acrylamide prepolymer solution dropwise to the soybean protein aqueous dispersion, stirring at room temperature for 1 hour, and mixing thoroughly to obtain a soybean protein-acrylamide prepolymer;

[0057] (4) adding 3 g of calcium sulfoaluminate to the soy protein-acrylamide prepolymer and hydrating for 30 min to obtain a soy protein-acrylamide-hydrated calcium sulfoaluminate aqueous dispersion;

[0058] (5) The dispersion was allowed to stand at room temperature for 2.5 h to thermally initiate free radical polymerization of acrylamide to generate soybean protein-polyacrylamide chain entanglement polymers.

[0059] Example 4

[0060] This embodiment provides a method for preparing a soybean protein-polyacrylamide chain entanglement polymer, the main steps of which are:

[0061] (1) In a 250 mL stirred reactor, 30 g of soybean protein powder was dissolved in 100 mL of distilled water and stirred at room temperature for 1 h to fully soak the soybean protein powder;

[0062] After heat denaturation at 90°C for 4 h, a light yellow soy protein aqueous dispersion was obtained;

[0063] (2) dissolving 35 g of acrylamide monomer and 0.525 g of ammonium persulfate initiator in 40 mL of distilled water and stirring the mixture at room temperature for 1 h to obtain an acrylamide prepolymer solution;

[0064] (3) adding the acrylamide prepolymer solution dropwise to the soybean protein aqueous dispersion, stirring at room temperature for 1 hour, and mixing thoroughly to obtain a soybean protein-acrylamide prepolymer;

[0065] (4) adding 5.25 g of calcium sulfoaluminate to the soy protein-acrylamide prepolymer and hydrating for 30 min to obtain a soy protein-acrylamide-hydrated calcium sulfoaluminate aqueous dispersion;

[0066] (5) The dispersion was allowed to stand at room temperature for 2.5 h to thermally initiate free radical polymerization of acrylamide to generate soybean protein-polyacrylamide chain entanglement polymers.

[0067] Example 5

[0068] This embodiment provides a method for preparing a soybean protein-polyacrylamide chain entanglement polymer, the main steps of which are:

[0069] (1) In a 250 mL stirred reactor, 30 g of soybean protein powder was dissolved in 100 mL of distilled water and stirred at room temperature for 1 h to fully soak the soybean protein powder;

[0070] After heat denaturation at 90°C for 4 h, a light yellow soy protein aqueous dispersion was obtained;

[0071] (2) dissolving 40 g of acrylamide monomer and 0.8 g of ammonium persulfate initiator in 40 mL of distilled water and stirring the mixture at room temperature for 1 h to obtain an acrylamide prepolymer solution;

[0072] (3) adding the acrylamide prepolymer solution dropwise to the soybean protein aqueous dispersion, stirring at room temperature for 1 hour, and mixing thoroughly to obtain a soybean protein-acrylamide prepolymer;

[0073] (4) adding 8 g of calcium sulfoaluminate to the soy protein-acrylamide prepolymer and hydrating for 30 min to obtain a soy protein-acrylamide-hydrated calcium sulfoaluminate aqueous dispersion;

[0074] (5) The dispersion is allowed to stand at room temperature for 2 h to thermally initiate free radical polymerization of acrylamide to generate soybean protein-polyacrylamide chain entanglement polymers.

[0075] The microstructure of the polymer Figure 1 As shown in the 3D tomography and scanning electron microscope photos ( Figure 1 a, b) show that the polymer presents a chain entanglement network structure, in which rod-shaped calcium sulphoaluminate hydrate micro-nano crystals are evenly dispersed in the skeleton structure, serving as entanglement sites to form a high degree of chain entanglement in the polyacrylamide macromolecular chain. At the same time, the element distribution diagram ( Figure 1 c, d) further confirmed that the carbon element (C) of the polyacrylamide macromolecular chain is highly entangled with the calcium element (Ca) of the calcium sulfoaluminate hydrate crystals.

[0076] Example 6

[0077] Analysis of tensile properties of soybean protein-polyacrylamide chain entanglement polymer:

[0078] The tensile properties of soy protein-polyacrylamide chain entanglement polymers were evaluated by analyzing the tensile stress-strain behavior of the samples.

[0079] The soy protein-polyacrylamide chain entanglement polymers prepared in the above Examples 1, 2, 3, 4 and 5 were cut into rectangular samples (length × width × thickness = 10 × 20 × 2 mm); then, a tensile fracture test was performed on the samples using an electronic universal testing machine with a load of 1 kN to obtain a tensile-strain curve, and thereby obtain the Young's modulus, tensile fracture stress and fracture strain of the samples.

[0080] The tensile test was carried out at room temperature with a tensile rate of 50 mm / min. Figure 2 By comparing Examples 1, 2, 3, 4, and 5, it can be seen that as the chain entanglement density increases, the elongation at break increases from 560% to 1100%, and the tensile stress increases from 34 kPa to 453 kPa. This shows that the introduction of the chain entanglement structure improves the tensile strength of the soy protein adhesive.

[0081] Example 7

[0082] Toughness analysis of soy protein-polyacrylamide chain entanglement polymer:

[0083] The toughness behavior of soy protein-polyacrylamide chain entanglement polymers was analyzed by tensile fracture tests of unnotched and notched samples, and the toughness was evaluated by calculating the tear energy.

[0084] The soy protein-polyacrylamide chain entanglement polymers prepared in the above Examples 1, 2, 3, 4 and 5 were cut into non-notched samples (length × width × thickness = 10 × 20 × 2 mm) and notched samples (length × width × thickness = 10 × 20 × 2 mm, notch width = 10 mm), respectively; then, the non-notched and notched samples were subjected to tensile fracture tests using an electronic universal testing machine with a load of 1 kN to obtain tension-displacement curves, with a tensile rate of 50 mm / min. The coating area was determined based on the non-notched tension and the displacement at which the notch crack began to expand, and the tearing energy was calculated.

[0085] The test results are as follows Figure 3 By comparing Examples 1, 2, 3, 4, and 5, it can be seen that as the chain entanglement density increases, the tear energy increases from 265 J / m 2 Increased to 4100 J / m 2 This shows that the introduction of chain entanglement structure significantly enhances the toughness of soybean protein adhesive.

[0086] Example 8

[0087] Anti-fatigue properties and hysteresis analysis of soy protein-polyacrylamide chain entanglement polymers:

[0088] The fatigue resistance and hysteresis of soy protein-polyacrylamide chain entanglement polymers were evaluated and analyzed by multiple cyclic tensile tests.

[0089] The sample was subjected to a cyclic tensile test using an electronic universal testing machine with a load of 1kN. The sample was stretched to a set elongation strain at a constant rate (50mm / min) at room temperature, and then the strain was released to 0% at the same rate to restore the sample to its initial state. This process was repeated many times to obtain a cyclic stress-strain curve, from which the stress retention rate, plastic deformation rate and energy dissipation coefficient of the sample during the cyclic loading-unloading process were calculated.

[0090] The fatigue resistance and hysteresis of the samples were evaluated by analyzing the changes in stress retention rate, plastic deformation rate and energy dissipation coefficient during multiple cycles.

[0091] The soy protein-polyacrylamide chain entanglement polymer prepared in Example 5 was subjected to a continuous 100-time stretch-release cycle test. The results are as follows: Figure 4 shown.

[0092] It can be seen from this that during 100 cycles of stretching, the maximum tensile stress of the soy protein-polyacrylamide chain entanglement polymer is maintained at ~22 kPa, the plastic deformation rate is ~6%, the energy dissipation coefficient is maintained below ~0.06, and the hysteresis is maintained below 6%, indicating that the chain entanglement polymer gel has both low hysteresis and anti-fatigue properties.

[0093] Example 9

[0094] Soy protein-acrylamide-calcium sulfoaluminate hydrate aqueous dispersion used for bonding properties of eucalyptus veneer:

[0095] The soy protein-acrylamide-calcium sulfoaluminate hydrate aqueous dispersion prepared in Example 5 was used as a modified adhesive and subjected to "coating → pre-pressing → hot pressing" on a eucalyptus veneer to obtain a three-layer eucalyptus plywood.

[0096] The specific pressing process of three-layer eucalyptus plywood is as follows: three eucalyptus veneers are selected as the upper surface board, the lower surface board and the core board respectively, and the soy protein-acrylamide-hydrated calcium sulfoaluminate aqueous dispersion is coated on the surface of the eucalyptus veneer respectively, among which the upper surface board and the lower surface board are coated on one side, and the core board is coated on both sides, and the glue amount on one side is 160-180g / m 2; Then assemble the coated upper surface plate, core plate and lower surface plate in sequence along the direction perpendicular to the wood grain, and pre-press on a flat vulcanizer (normal temperature, pressure 1MPa, pre-press time 1h); then hot press on a flat vulcanizer (120℃, pressure 1MPa, hot pressing time 405s); cool to room temperature to obtain a three-layer eucalyptus plywood.

[0097] The three-layer eucalyptus plywood was prepared by using the above-mentioned pressing process and ordinary soy protein adhesive as the control group. The mechanical properties of the two plywoods, such as wet bonding strength and immersion peeling, were tested using the test method for Class II plywood in GB / T 9846-2015 "Ordinary Plywood".

[0098] Depend on Figure 5 From a and b, we can see that compared with ordinary soybean protein adhesive, this adhesive exhibits excellent coating performance; Figure 5 c (wherein 1 represents the mechanical properties of the three-layer eucalyptus plywood prepared with ordinary soy protein adhesive, and 2 represents the mechanical properties of the three-layer eucalyptus plywood prepared with the adhesive prepared in Example 5). It can be seen that compared with the three-layer eucalyptus plywood pressed with ordinary soy protein adhesive, the three-layer eucalyptus plywood pressed with the adhesive developed by the present invention shows satisfactory bonding performance, the wet bonding strength is increased by 167%, and the wood breakage rate is increased from 20% to 90%.

[0099] Comparative Example 1

[0100] This embodiment provides a method for preparing a soybean protein-polyacrylamide chain entanglement polymer, the main steps of which are:

[0101] (1) In a 250 mL stirred reactor, 20 g of soybean protein powder was dissolved in 100 mL of distilled water and stirred at room temperature for 1 h to fully soak the soybean protein powder;

[0102] After heat denaturation at 90°C for 4 h, a light yellow soy protein aqueous dispersion was obtained;

[0103] (2) dissolving 20 g of acrylamide monomer and 0.12 g of ammonium persulfate initiator in 40 mL of distilled water and stirring the mixture at room temperature for 1 h to obtain an acrylamide prepolymer solution;

[0104] (3) then dropping the acrylamide prepolymer solution into the soybean protein aqueous dispersion, stirring at room temperature for 1 hour, and fully mixing to obtain a soybean protein-acrylamide prepolymer;

[0105] (4) adding 0.25 g of calcium sulfoaluminate to the soy protein-acrylamide prepolymer and hydrating for 30 min to obtain a soy protein-acrylamide-hydrated calcium sulfoaluminate aqueous dispersion;

[0106] (5) The dispersion was allowed to stand at room temperature for 4 h to thermally initiate free radical polymerization of acrylamide to generate soybean protein-polyacrylamide chain entanglement polymers.

[0107] Comparative Example 2

[0108] This embodiment provides a method for preparing a soybean protein-polyacrylamide chain entanglement polymer, the main steps of which are:

[0109] (1) In a 250 mL stirred reactor, 30 g of soybean protein powder was dissolved in 100 mL of distilled water and stirred at room temperature for 1 h to fully soak the soybean protein powder;

[0110] After heat denaturation at 90°C for 4 h, a light yellow soy protein aqueous dispersion was obtained;

[0111] (2) dissolving 40 g of acrylamide monomer and 0.8 g of ammonium persulfate initiator in 40 mL of distilled water and stirring the mixture at room temperature for 1 h to obtain an acrylamide prepolymer solution;

[0112] (3) adding the acrylamide prepolymer solution dropwise to the soybean protein aqueous dispersion, stirring at room temperature for 1 hour, and mixing thoroughly to obtain a soybean protein-acrylamide prepolymer;

[0113] (4) adding 10.5 g of calcium sulfoaluminate to the soy protein-acrylamide prepolymer and hydrating for 30 min to obtain a soy protein-acrylamide-hydrated calcium sulfoaluminate aqueous dispersion;

[0114] (5) The dispersion is allowed to stand at room temperature for 2 h to thermally initiate free radical polymerization of acrylamide to generate soybean protein-polyacrylamide chain entanglement polymers.

[0115] The soy protein-polyacrylamide chain entanglement polymers prepared in the above Comparative Examples 1 and 2 were cut into non-notched samples (length × width × thickness = 10 × 20 × 2 mm) and notched samples (length × width × thickness = 10 × 20 × 2 mm, notch width = 10 mm), respectively; then, the non-notched and notched samples were subjected to tensile fracture tests using an electronic universal testing machine with a load of 1 kN to obtain tension-displacement curves, with a tensile rate of 50 mm / min. The covering area was determined based on the non-notched tension and the displacement at which the notch crack began to expand, and the tearing energy was calculated.

[0116] The test results are as follows Figure 6 From comparative examples 1 and 2, it can be seen that when the mass ratio of calcium sulfoaluminate to acrylamide is not properly controlled, the tear energy of the prepared polymer is only 90 J / m 2 Within, showing little toughness.

[0117] The soy protein-polyacrylamide chain entanglement polymers prepared in the above comparative examples 1 and 2 were subjected to 100 consecutive stretch-release cycle tests. The results are as follows: Figure 6 As shown in b. It can be seen that when the mass ratio of calcium sulfoaluminate to acrylamide is not properly controlled, the prepared polymer has a plastic deformation rate of >12%, an energy dissipation coefficient of >0.26, and a hysteresis of more than 26% during 100 cycles of stretching, showing high hysteresis and fatigue resistance.

[0118] The present invention provides a soy protein adhesive with low hysteresis and high toughness, and a preparation method and application thereof. The metal coordination effect of calcium sulfoaluminate hydrate is used to induce entanglement of polyacrylamide macromolecular chains, construct a soy protein-polyacrylamide chain entanglement polymer, and transmit external stress and dissipate energy through the sliding of entanglement sites, thereby improving the toughness of the adhesive layer under low hysteresis; at the same time, the polyacrylamide chain entanglement formed at the wood interface forms a large number of hydrogen bonds with the wood and the adhesive layer, respectively, generating strong binding energy, thereby improving the interfacial force between the adhesive and the wood. The present invention introduces a chain entanglement structure into the soy protein adhesive system to construct a network structure integrating protein and chain entanglement polymers, which helps to solve the problem of brittle cured adhesive layer and weak interfacial force with wood, and provides technical support for improving the quality of artificial board products and promoting the large-scale application of soy protein adhesives.

[0119] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the present invention.

Claims

1. A method for preparing a low hysteresis and high toughness soybean protein adhesive, characterized in that: include, The soy protein powder is mixed with distilled water to obtain a mixed solution, and the mixed solution is subjected to a heating treatment to obtain a soy protein water dispersion, wherein the concentration of the soy protein in the mixed solution is 0.2-0.3 g / mL; At room temperature, acrylamide and ammonium persulfate are dissolved in distilled water, and the mixture is fully stirred to dissolve to obtain an acrylamide prepolymer solution, wherein the mass ratio of acrylamide to ammonium persulfate is 1:0.006-1:0.02, and the concentration of acrylamide in the acrylamide prepolymer solution is 0.5-1 g / mL; Dropping the acrylamide prepolymer solution into the soy protein aqueous dispersion, stirring and fully mixing at room temperature, to obtain a soy protein-acrylamide prepolymer; At room temperature, adding inorganic calcium sulfoaluminate powder to soy protein-acrylamide prepolymer and fully dispersing to obtain soy protein-acrylamide-hydrated calcium sulfoaluminate water dispersion, wherein the mass ratio of calcium sulfoaluminate powder to acrylamide is 2-20:100; The soy protein-acrylamide-calcium sulfoaluminate hydrate aqueous dispersion was left to stand at room temperature for 2-4 h. The calcium sulfoaluminate underwent hydration reaction to generate calcium sulfoaluminate hydrate nanocrystals and release heat. The acrylamide monomer was thermally initiated to polymerize to generate polyacrylamide macromolecular chains. The Al 3+ , Ca 2+ Through coordination, the polyacrylamide macromolecular chains are induced to entangle around the crystals, forming polyacrylamide chain entanglements with calcium sulfoaluminate hydrate as the entanglement sites. At the same time, the carboxyl groups on the soy protein particles are aggregated around the polyacrylamide chains through intermolecular forces, forming soy protein-polyacrylamide chain entanglement polymers.

2. The preparation method according to claim 1, characterized in that: The soy protein water dispersion is obtained by the heating treatment, wherein the heating temperature is 90-95° C. and the stirring is performed for 4-5 hours.

3. The soybean protein adhesive with low hysteresis and high toughness obtained by the preparation method according to claim 1 or 2.

4. The soybean protein adhesive according to claim 3, characterized in that: The soy protein adhesive has a hysteresis of less than 6% and a tear energy of 4100 J / m 2 , tensile stress to 453 kPa.

5. Use of the low hysteresis and high toughness soybean protein adhesive according to claim 3 as an adhesive for wood.

Citation Information

Patent Citations

  • Novolac epoxy resin soybean protein adhesive as well as preparation method and application thereof

    CN113861937A

  • Adhesion promoting agent for a thermal insulation surface

    CN1890338A